Synthesis, Characterization and Anti-Trypanosoma Cruzi Evaluation of Ferrocenyl and Cyrhetrenyl Imines Derived from 5-Nitrofurane - Godoy-Gonzalez, F; Godoy-Gonzalez, F (2011)
A series of new cyrhetrenyl and ferrocenylimines complexes derived from 5-nitrofurane were designed, synthesized and characterized. The 1H and 13C NMR spectra indicate that these compounds adopt an anti-(E) conformation in solution, and confirmed for 1b by the X-ray crystal crystallography. The electronic effects of cyrhetrenyl (1b) and ferrocenyl (1a) bound directly to nitrogen have been correlated with the chemical shift of the iminic carbon. The trypanocidal activity (Tulahuen strain of Trypanosoma cruzi) of these compounds has been studied with respect to the substituent on the nitrogen atom of the 5-nitrofurfurylideneamino pharmacophore. Even though all the resulting derivatives were less active than Nifurtimox, the cyrhetrenyl complex (1b), compared with ferrocenyl (1a) or purely organic (4a and 4b) analogues, was more efficient as antichagasic agent. This result is likely due to the enhanced lipophilic character of the molecules or from a possible synergy between the cyrhetrenyl and 5-nitrofurane groups. © 2011 Elsevier B.V. All rights reserved.